2022
DOI: 10.3390/plants11152026
|View full text |Cite
|
Sign up to set email alerts
|

Application of Silica Nanoparticles in Combination with Two Bacterial Strains Improves the Growth, Antioxidant Capacity and Production of Barley Irrigated with Saline Water in Salt-Affected Soil

Abstract: Exploitation of low-quality water or irrigation of field crops with saline water in salt-affected soil is a critical worldwide challenge that rigorously influences agricultural productivity and sustainability, especially in arid and semiarid zones with limited freshwater resources. Therefore, we investigated a synergistic amendment strategy for salt-affected soil using a singular and combined application of plant growth-promoting rhizobacteria (PGPR at 950 g ha−1; Azotobacter chroococcum SARS 10 and Pseudomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 68 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Salinity not only disintegrates the chlorophyll structure and integrity but also denatures enzymes responsible for chlorophyll biosynthesis, hence leading to a decrease in chlorophyll content of leaves, growth, and yield (Mugwanya et al 2022 ; Nawaz et al 2022 ). Similar results have previously been reported in Oryza sativa L. (Hakim et al 2014 ; Kumar et al 2021 ), Triticum aestivum (Eroglu et al 2020 ; Adil et al 2022 ), Hordeum vulgare L. (Noreen et al 2021 ; Alharbi et al 2022 ), and Zea mays (Bouras et al 2021 ; Ali et al 2022 ).…”
Section: Discussionsupporting
confidence: 82%
“…Salinity not only disintegrates the chlorophyll structure and integrity but also denatures enzymes responsible for chlorophyll biosynthesis, hence leading to a decrease in chlorophyll content of leaves, growth, and yield (Mugwanya et al 2022 ; Nawaz et al 2022 ). Similar results have previously been reported in Oryza sativa L. (Hakim et al 2014 ; Kumar et al 2021 ), Triticum aestivum (Eroglu et al 2020 ; Adil et al 2022 ), Hordeum vulgare L. (Noreen et al 2021 ; Alharbi et al 2022 ), and Zea mays (Bouras et al 2021 ; Ali et al 2022 ).…”
Section: Discussionsupporting
confidence: 82%
“…5a). In a similar vein, numerous studies have shown that silicon nanoparticles increase the antioxidant activity of various crops [51], [52], [53], [54]. Thus, potassium silicate treatment increases SOD, glutathione reductase [19], and catalase activities [55], slightly balancing the negative effects of drought on plants.…”
Section: Discussionmentioning
confidence: 93%
“…This, in turn, modulates different biochemical and molecular signal transducing pathways, resulting in improved signal perception and, as a result, increased growth and yield potential ( Bhatt et al, 2020 ). However, recent evidence suggests that the coupling effect of plant probiotics (PPs) and NMs may play an excellent role in managing abiotic stress ( Azmat et al, 2022 ; Muhammad et al, 2022 ; Alharbi et al, 2022a , b ). The combo effect of NMs and PPs exhibits various stress ameliorating effects by improving levels of photosynthetic pigments, activities of antioxidant enzymes, total soluble sugars, and reducing stress markers such as MDA content and electrolytic leakage in plants under salt stress ( Yasmin et al, 2021 ; Alharbi et al, 2022a ) and drought stress ( Akhtar et al, 2021 ; Azmat et al, 2022 ).…”
Section: Combo Of Nanomaterials and Plant Probiotics In The Mitigatio...mentioning
confidence: 99%
“…However, recent evidence suggests that the coupling effect of plant probiotics (PPs) and NMs may play an excellent role in managing abiotic stress ( Azmat et al, 2022 ; Muhammad et al, 2022 ; Alharbi et al, 2022a , b ). The combo effect of NMs and PPs exhibits various stress ameliorating effects by improving levels of photosynthetic pigments, activities of antioxidant enzymes, total soluble sugars, and reducing stress markers such as MDA content and electrolytic leakage in plants under salt stress ( Yasmin et al, 2021 ; Alharbi et al, 2022a ) and drought stress ( Akhtar et al, 2021 ; Azmat et al, 2022 ). Recently Etesami et al (2022) deciphered how the combination of nanosilicon and arbuscular mycorrhiza can be a prolific tactic to mitigate environmental stresses in crops and achieve sustainable plant productivity.…”
Section: Combo Of Nanomaterials and Plant Probiotics In The Mitigatio...mentioning
confidence: 99%